Reconnecting Europe's rivers the smart way. (Research'eu results magazine)
Barriers on Europe's rivers can improve fishing, be a source of energy and reduce the passage of invasive species, but they can also be a flood risk, interfere with migration patterns and fragment habitats. So what's the best approach to reconnecting our rivers? One EU-funded project is providing some answers.